2017
DOI: 10.1186/s12889-017-4154-6
|View full text |Cite
|
Sign up to set email alerts
|

Fun, influence and competence—a mixed methods study of prerequisites for high school students’ participation in physical education

Abstract: BackgroundMany adolescents do not reach the recommended levels of physical activity (PA), and students attending vocational studies are less committed to take part in physical education (PE) than other students. The purpose of the present study was twofold: 1) to examine differences in physical activity, diet, smoking habits, sleep and screen time among Norwegian vocational high school students who selected either a PE model focusing on PA skills, technique and improvement of physical performance (“Sports enjo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…[36][37][38] Further research is needed to encourage girls to participate in curricular and noncurricular physical activities and identify strategies to maximize movement and fun. 37,39 Social (family, peers, community), physical (fast-food outlets, convenience stores, school, street vendors), and environmental factors influence the food choices and eating behavior of adolescents. [40][41][42] Previous studies have found that family meals during adolescence may have a lasting positive influence on dietary quality and meal patterns in young adulthood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[36][37][38] Further research is needed to encourage girls to participate in curricular and noncurricular physical activities and identify strategies to maximize movement and fun. 37,39 Social (family, peers, community), physical (fast-food outlets, convenience stores, school, street vendors), and environmental factors influence the food choices and eating behavior of adolescents. [40][41][42] Previous studies have found that family meals during adolescence may have a lasting positive influence on dietary quality and meal patterns in young adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…36 -38 Further research is needed to encourage girls to participate in curricular and noncurricular physical activities and identify strategies to maximize movement and fun. 37,39…”
Section: Discussionmentioning
confidence: 99%
“…Extracurricular coaches have an important responsibility in designing and implementing extracurricular programs that suit students' needs and interests (Abildsnes et al, 2017;Onyura et al, 2021). Extracurricular supervisors are responsible for preparing annual program plans and ensuring that each activity is well-planned (Kosarikov & Davydova, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…27 In addition, strategies to curb e-cigarette advertising and marketing appealing to young, physically active adolescents, and strategies to reduce access to flavored tobacco products by young people must be implemented. Physical education teachers, middle and high school sports team coaches, club sport coaches, and celebrities may have a unique role to play when it comes to tobacco prevention among the younger population by including EVP use behavior alongside healthy eating 28 and sleep behaviors, 29 particularly those engaging in physical activities.…”
Section: Discussionmentioning
confidence: 99%